2018
DOI: 10.1161/jaha.117.007267
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Risk of Myocardial Infarction Compared to Recurrent Stroke After Transient Ischemic Attack and Ischemic Stroke: Systematic Review and Meta‐Analysis

Abstract: BackgroundUncertainties remain about the current risk of myocardial infarction (MI) after ischemic stroke or transient ischemic attack.Methods and ResultsWe undertook a systematic review to estimate the long‐term risk of MI, compared to recurrent stroke, with temporal trends in ischemic stroke/transient ischemic attack patients. Annual risks and 95% confidence intervals (95% CI) of MI and recurrent stroke were estimated using random‐effect meta‐analyses. We calculated incidence ratios of MI/recurrent stroke, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
87
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 46 publications
6
87
4
3
Order By: Relevance
“…Given that our cohort was only composed of stroke patients who were much older (mean age ~ 77 years), it is likely that the gender differences in MI incidence rates observed in younger ages would not be present. 6 Nevertheless, our results are derived from real-world data and it is F I G U R E 3 Incidence curve illustrating the cumulative incidence of MI in the patient population over the entire follow-up period after hospital discharge likely that our estimates are accurate in the context of populations similar to our cohort receiving the same secondary prevention. 6,10,[21][22][23][24][25][26][27][28][29] Nevertheless, these studies appear to yield different risk factor profiles, likely due to the high between-study heterogeneity, as indicated by the most recent meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that our cohort was only composed of stroke patients who were much older (mean age ~ 77 years), it is likely that the gender differences in MI incidence rates observed in younger ages would not be present. 6 Nevertheless, our results are derived from real-world data and it is F I G U R E 3 Incidence curve illustrating the cumulative incidence of MI in the patient population over the entire follow-up period after hospital discharge likely that our estimates are accurate in the context of populations similar to our cohort receiving the same secondary prevention. 6,10,[21][22][23][24][25][26][27][28][29] Nevertheless, these studies appear to yield different risk factor profiles, likely due to the high between-study heterogeneity, as indicated by the most recent meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of 39 studies in patients with first transient ischaemic attack (TIA) or stroke, annual risks were 2.2% (95% CI: 1.7-2.7) for total MI, 0.9% (0.7-1.2) for non-fatal MI and 1.1% (0.8-1.5) for fatal MI. 6 Given that there is significant overlap between stroke secondary preventative therapies and acute coronary syndrome (ACS) primary prevention, it may not seem surprising that the annual incidence of post-stroke MI is not as high expected in such a highly co-morbid population. 5 The most recent systematic review calculated that the yearly risk of post-stroke MI is 1.67%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Despite progress and declining trends, recurrent stroke is still frequent. 4,5 Recurrent ischemic stroke (IS) has been associated with increased mortality and functional dependence, 6,7 but this remains insufficiently explored. 4,5 Recurrent ischemic stroke (IS) has been associated with increased mortality and functional dependence, 6,7 but this remains insufficiently explored.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, several studies conducted in a wide range of different settings have focused on the association between transient ischaemic attack (TIA) and the risk of stroke [3][4][5][6][7][8][9][10][11][12][13][14]. Whilst these results have shed some light on the association between TIA and stroke, they also have had several limitations that must be acknowledged.…”
Section: Introductionmentioning
confidence: 99%